Antimicrobial Properties of Colostrum and Milk - Furkan Eker; Emir Akdaşçi; Hatice Duman; Yalçın Mert Yalçıntaş; Ahmet Alperen Canbolat; Arda Erkan Kalkan; Sercan Karav; Dunja Šamec (MDPI AG, 2024)
The growing number of antibiotic resistance genes is putting a strain on the ecosystem and harming human health. In addition, consumers have developed a cautious attitude towards chemical preservatives. Colostrum and milk are excellent sources of antibacterial components that help to strengthen the immunity of the offspring and accelerate the maturation of the immune system. It is possible to study these important defenses of milk and colostrum, such as lactoferrin, lysozyme, immunoglobulins, oligosaccharides, etc., as biotherapeutic agents for the prevention and treatment of numerous infections caused by microbes. Each of these components has different mechanisms and interactions in various places. The compound's mechanisms of action determine where the antibacterial activity appears. The activation of the antibacterial activity of milk and colostrum compounds can start in the infant's mouth during lactation and continue in the gastrointestinal regions. These antibacterial properties possess potential for therapeutic uses. In order to discover new perspectives and methods for the treatment of bacterial infections, additional investigations of the mechanisms of action and potential complexes are required.